Ecological Evaluation on Several Green Open Spaces in Jakarta - Syarif Hidayat, Muhammad; ., . (International Journal of Engineering and Technology, 2018)
Urban development in the past until now tended to minimize the green open spaces and eliminate the natural feature. The condition of the urban environment become economically developed, but ecologically declined. Among environmental problems arise are rising urban air temperature, air pollution and declining soil absorption.Â This study aims to evaluate the environmental performance of the green space in the urban areas, especially in the Central and South of Jakarta, Indonesia. The area of study selected are considered the well-known green space in Jakarta, that is Menteng, andÂ Suropati Parks in the Central Jakarta and Ayodya and Langsat ParksÂ inÂ the South of Jakarta. The study is carried out through secondary data and field survey. The study indicates that Suropati, Langsat and Park have a potential in filtering air pollution because of their trees inside. Otherwise, Ayodya and Menteng have less because their trees are not so dense that the two parks before. The Langsat Park also has a potential in facing floods because of its positions and river pass by. The other three parks have similar role that is only absorbs water when floods occur. The microclimate condition also stands for Langsat parks because of its geographical position and trees surrounding in the area and inside are enough for reducing air temperature.Â Â